Een vroeg telescoopje uit Delft - Cocquyt, Tiemen (Studium, 2017)
An early spyglass from Delft Recently, a small spyglass was uncovered during archaeologic excavations in Delft. Remarkable about the find are its fashioning in sheet iron and the heavily stopped down objective lens. These are the presumed characteristics of Dutch telescopes from the early seventeenth century, none of which appear to have been preserved. This article sets out the results of the subsequent research on the object carried out in Museum Boerhaave, in which this suspicion was confirmed. Finally, a glimpse is offered on the mathematical-optical culture in Golden Age Delft, and a possible maker for the spyglass is put forward.